Available Extracorporeal Treatments for Poisoning: Overview and Limitations. Issue 4 (3rd April 2014) - Ouellet, Georges; Bouchard, Josée; Ghannoum, Marc; Decker, Brian Scott
Abstract Poisoning is a significant public health problem. In severe cases, extracorporeal treatments (ECTRs) may be required to prevent or reverse major toxicity. Available ECTRs include intermittent hemodialysis, sustained low‐efficiency dialysis, intermittent hemofiltration and hemodiafiltration, continuous renal replacement therapy, hemoperfusion, therapeutic plasma exchange, exchange transfusion, peritoneal dialysis, albumin dialysis, cerebrospinal fluid exchange, and extracorporeal life support. The aim of this article was to provide an overview of the technical aspects, as well as the potential indications and limitations of the different ECTRs used for poisoned patients.